Turbulent diffusion and drift in galactic magnetic fields and the explanation of the knee in the cosmic ray spectrum - Candia, Julián Marcelo (2002)
We reconsider the scenario in which the knee in the cosmic ray spectrum is explained as due to a change in the escape mechanism of cosmic rays from the galaxy from one dominated by transverse diffusion to one dominated by drifts. We solve the diffusion equations adopting realistic galactic field models and using diffusion coefficients appropriate for strong turbulence (with a Kolmogorov spectrum of fluctuations) and consistent with the assumed magnetic fields. We show that properly taking into account these effects leads to a natural explanation of the knee in the spectrum, and a transition towards a heavier composition above the knee is predicted.